An empirical assessment of business cycle asymmetries: evidence from Malaysia - Abdul Manap, Turkhan Ali (Universiti Malaysia Sarawak, 2010)
Asymmetry is a key feature to understand the different behavior of expansions and recessions, and it provides a stylized fact that business cycle models should help to explain. Furthermore, the types of asymmetries provide guidance about underlying economic mechanism. In this paper, we test for three types of asymmetry of business cycle: steepness, deepness and sharpness, by using the parametric tests of Clements and Krolzig (2003), based on Markov-Switching autoregressive models in the real GDP of Malaysia for the period from 1975Q1 to 2006Q4. This paper also uses three different approaches to remove trend component of GDP to investigate the sensitivity of the findings of asymmetries to the method of trend eliminations. Finally, for comparison, the non-parametric test of Randles et al. (1980) is also employed. We find strong evidence of steep asymmetry but not deep sharp asymmetry for Malaysia which is in contrast to the findings of Khong and Lau (2007) and Eng and Wang (2008). These findings have important implications for econometric modeling and policy making.